1986
DOI: 10.1002/jso.2930320310
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of preoperative serum cea level compared to clinical staging IV. Histological grading and tumor type in colorectal and gastric cancer

Abstract: In a clinical investigation of observed postoperative survival, 410 patients with colorectal cancer and 269 patients with stomach cancer have been registered for primary surgical treatment connected with a long-term follow up. Histologic grading and tumor typing were examined as potential prognostic factors and compared with the prognostic information covered by operability, tumor extension, and the preoperative CEA level. Statistical treatment of the data revealed no prognostic significance of the tumor types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Consistent with the Kodera et al study [6], differentiated tumors in our series tended to show a higher rate in CEA positive patients; however, the difference was not statistically signi®cant. Other investigators found no correlation between CEA and histologic type [13,16,19]. The differences between reports addressing histologic type and these tumor markers may be due to the variation of histologic types in differentiated and undifferentiated tumor groups and the different rates of these histologic types in different series.…”
Section: Discussionmentioning
confidence: 91%
“…Consistent with the Kodera et al study [6], differentiated tumors in our series tended to show a higher rate in CEA positive patients; however, the difference was not statistically signi®cant. Other investigators found no correlation between CEA and histologic type [13,16,19]. The differences between reports addressing histologic type and these tumor markers may be due to the variation of histologic types in differentiated and undifferentiated tumor groups and the different rates of these histologic types in different series.…”
Section: Discussionmentioning
confidence: 91%
“…HRs and 95% CIs were available in 19 studies[38,39,40,24,41,13,25,42,20,43,21,44,45,46,47,37,48,49,50]. In the remaining studies, the values were extracted from the published survival curves in 14 studies[51,35,52,12,53,54,55,56,17,11,16,57,23,58], and estimated from the variance and its P -value (the Log-rank test) from one study[36] using the statistical methods previously reported[26]. The pooled HR and 95% CI values of these 34 studies were estimated (HR 1.786, 95% CI 1.550–2.060), but significant heterogeneity was observed among these studies with respect to OS ( I 2 = 77.7%, n = 34, P < 0.001: Table 2).…”
Section: Resultsmentioning
confidence: 99%